Stimulating Visit Intention Using Social Media Influencer: Mediating Role of Enjoyment - Yusra; Vilzati; Eliana; Ariffin, Ahmad Azmi Mohd; Susanto, Perengki (School of Business, IPB University (SB-IPB), 2023)
Social media influencer (SMI) has emerged as one of a powerful approach in building customer’s intention to visit a tourism destination. This research therefore tries to uncover the mechanism on how the dimensions of SMI, namely attractiveness, trustworthiness, and expertise, influence visit intention by incorporating enjoyment as mediator by applying Stimuli-Organism-Response (SOR) Theory. Using purposing sampling, 115 usable samples of those who experienced an SMI’s posts regarding Aceh tourism, are gathered online. Data were analyzed by using Partial Least Square-Structural Equation Modelling (PLS-SEM). In testing the hypotheses, we conduct a Bootstrapping procedure using 5000 sub-samplings. The finding highlights that SMIs’ attractiveness and SMIs’ expertise, are found to be a strong predictor of enjoyment, of which has a significant relationship with visit intention. However, SMI trustworthiness failed to predict enjoyment. Except for SMI trustworthiness-visit intention relationship, this study also found the role of enjoyment as mediator for both SMI attractiveness and SMI expertise in predicting visit intention. Consequently, this research pinpoints two routes to obtaining visitors’ intention to visit a tourism site. They are attractiveness-enjoyment-intention and expertise-enjoyment-intention with the second pathway have bigger contribution to visit intention. The findings can be used as a guide to assist tourism destination marketers in developing effective advertising that use SMI to communicate with their visitor and differentiate themselves from the tourism destination intense competition. Keywords: social media influencers, enjoyment, visit intention, sor theory, tourism destination